Long-term survival after multidisciplinary treatments for HER2-positive advanced gastric cancer with multiple liver and lung metastases - Satoshi Yoshioka; Naoto Takahashi; Muneharu Fujisaki; Kenji Takeshita; Yuta Takano; Fumiaki Yano; Naoki Toya; Ken Eto (Surgical Case Reports)
Abstract Background Trastuzumab-based chemotherapy is a standard treatment regimen for human epithelial growth factor 2 (HER2)-positive gastric cancer. This is a case of a patient who has survived 12 years after being diagnosed with advanced gastric cancer with multiple liver and lung metastases. Case presentation A woman in her 70s underwent total gastrectomy, cholecystectomy, and left hepatic lobectomy for gastric cancer with liver metastasis. One month after the surgery, multiple liver metastases appeared. After two courses of S-1 + CDDP chemotherapy, the liver metastases disappeared, and new lung metastases occurred. Because the primary tumor was HER2 positive, S-1 + CDDP + trastuzumab chemotherapy was performed. After one course of chemotherapy, the blood test showed pancytopenia, and CDDP was discontinued. S-1 + trastuzumab chemotherapy was then initiated, and as a result, the lung metastases disappeared. The patient is alive without recurrence 12 years after the surgery. Conclusions We encountered a case of long-term survival after multidisciplinary treatments for HER2-positive advanced gastric cancer with multiple liver and lung metastases.